Light heat and sound energy: viva education:science works for kids series - Moore, Jo Ellen (Viva Education New Delhi, 2004)
This educational title explores the concepts of light, heat, and sound energy in a fun and accessible manner. With engaging illustrations and simple experiments, it helps young readers understand how these forms of energy affect our everyday lives and the natural world.